Social considerations to make data FAIR-er: Understanding researchers’ views on data “misuse” and credit - Winthrop, Samuel (Septentrio Conference Series, 2019)
While community infrastructure initiatives work to make it easier for researchers to manage and share their data, two cultural and social factors require our attention. Just 9% of researchers feel they get sufficient credit for data sharing, according to the 2018 State of Data survey. In the same survey, researcher’s concern about “misuse” of their data was the leading reason given for not sharing data. The 2019 State of Open Data survey (forthcoming, 2019) digs into both topics in more detail. Using this new data, this poster will outline researcher attitudes and concerns, exploring what researchers mean by “misuse”, their views on credit, and how we can practically address them.